Implementasi Kurikulum 2013 Terhadap Rencana Pelaksanaan pembelajaran Bahasa Indonesia Kelas I, II, dan III Semester Gasal SDN Kebonsari 04 Jember Tahun pelajaran 2019/2020 - Indah dyah reformei; hari satrijono; fitria kurniasih (INVENTA: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
The replacement of the old curiculum until now the new curiculum requires careful preparation from various aspects both directly. One of them is the readiness of the teacher in designing the Learning Implementation Plan (RPP). This study aims to describe the result of the study of the Indonesian Language Learning Plan (RPP) classes I, II and III at SDN Kebonsari 04 Jember odd semester 2019/2020. This type of research is descriptive qualitatif. The instrument of the researcher himself, the questionnaire sheet, the document notes were assessed by a checklist based on the rubik assessment used to collect data in the form of the result of the questionnaire sheet study and interview guidelines. The result showed that the suitability of the RPP component to the 2013 curiculum in RPP 1 with a value 56, RPP 2 with a value of 57, RPP 3 with a value of 59, RPP 4 with a value of 59, RPP 5 with a value of 60, RPP 6 with a value of 68. Based on the relevance study in the form of indicators, adequacy of materials, learning activities, learning objective and assessment of learning outcomes obtained RPP 1 (52,9%), RPP 2 (70,5%), RPP 3 (76,4%), RPP 4 (76,4%), RPP 5 (76,4%), RPP 6 (94,1%).